The comparison of ultrasound and non-contrast helical computerized tomography for children nephrolithiasis detection - Majid Malaki (Urology Annals, 2014)
Aims: Nephrolithiasis is less common in children than adults, but its diagnosis and management in children may be more perplexing. In this article, we compare two imaging ultrasound (US) and non-contrast helical computerized tomography (CT) for diagnosis of nephrolithiasis. Subjects and Methods: A total of 20 children who diagnosed as nephrolithiasis by US were imaged simultaneously by non-contrast helical CT. Their history like as family history in first and second degree relatives and urine analysis for hematuria and urine randomly calcium to creatinine ratio was obtained. All data analyzed by χ2 and Mann-Whitney U-test in SPSS 16 and P < 0.05 was considered to be significant. Results: Out of 20 cases, only 5 cases diagnosed as nephrlithiasis by US were confirmed by CT method 2 out of 20 cases had another extrarenal origin for their complaint who diagnosed wrongly as nephrolithiasis by US. Stone size based of US that was confirmed by CT method was larger 4.6 ± 1.5 (minimum 3 max 6 mm) than non-confirmed ones 2.3 ± 0.7 mm (P 0.002). Hematuria occurred more in correct diagnosed compared with misdiagnosed (P 0.005). Positive family history and urine calcium ratio was not differed between two groups. Conclusions: Non contrast helical CT is essential to confirm of nephrolithiasis and other extrarenal origin of complaints, which diagnosed wrongly as nephrolithiasis in children. Stone size and presence of hematuria are two major factors for right diagnosis of nephrolithiasis as US method but Urine calcium excretion ratio or positive family history cannot be predictive as this study.